2016
DOI: 10.1252/jcej.15we111
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Calcium Phosphates from Composted Chicken Manure

Abstract: To recover phosphorus from composted chicken manure, a batch method with aqueous HNO 3 , HCl and H 2 SO 4 was used to examine the elution behavior of the aqueous calcium and phosphate contained in the manure. Since the main components in manure are Ca 2+ and K + along with PO 4 3and those ions can be dissolved using an acidic eluate, it was expected that most of the aqueous Ca 2+ , K + and PO 4 3could be obtained via the elution. Therefore, it seemed plausible that the removal of the aqueous K + obtained by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…However, BCF altered the composition of moderately labile P in this study, and 1 M HCl‐Pi gradually dominated with increasing grazing density (Figure 2b). This observation can be linked to three possible phenomena: (a) the deposition of chicken manure gradually increases soil pH with increasing grazing density (Somda, Powell, & Bationo, 1997), which reduces the adsorption performance of iron–aluminum oxides (Yan, Wang, Liu, & Feng, 2019) and prevents it from complexing with more free phosphorus; (b) the stability of HCl‐extracted P is strongly dependent on soil pH, and HCl‐extracted P pools in high‐pH soils tend to contain highly stable calcium phosphate minerals (Helfenstein et al, 2020; Hou, Lu, Jiang, Wen, & Luo, 2019); and (c) the higher Ca 2+ in chicken manure may complex with dissolved Pi in the soil to form 1 M HCl‐Pi (Sugiyama et al, 2016). In synthesis, the P fraction was influenced by grazing density, and an increase in labile and moderately labile P increased the soil P availability and supply capacity in the BCF system.…”
Section: Discussionmentioning
confidence: 99%
“…However, BCF altered the composition of moderately labile P in this study, and 1 M HCl‐Pi gradually dominated with increasing grazing density (Figure 2b). This observation can be linked to three possible phenomena: (a) the deposition of chicken manure gradually increases soil pH with increasing grazing density (Somda, Powell, & Bationo, 1997), which reduces the adsorption performance of iron–aluminum oxides (Yan, Wang, Liu, & Feng, 2019) and prevents it from complexing with more free phosphorus; (b) the stability of HCl‐extracted P is strongly dependent on soil pH, and HCl‐extracted P pools in high‐pH soils tend to contain highly stable calcium phosphate minerals (Helfenstein et al, 2020; Hou, Lu, Jiang, Wen, & Luo, 2019); and (c) the higher Ca 2+ in chicken manure may complex with dissolved Pi in the soil to form 1 M HCl‐Pi (Sugiyama et al, 2016). In synthesis, the P fraction was influenced by grazing density, and an increase in labile and moderately labile P increased the soil P availability and supply capacity in the BCF system.…”
Section: Discussionmentioning
confidence: 99%
“…e study revealed that calcium phosphate and calcium hydroxyapatite could be easily recovered by ammoniatreatment of the nitric acid extract from the incineration ash of chicken manure (Sugiyama et al, 2019(Sugiyama et al, , 2020 and from composted chicken manure (Sugiyama et al, 2016). We established that chicken manure could be used as a new phosphorus resource.…”
Section: Introductionmentioning
confidence: 95%
“…It is estimated that approximately 457 million tons of CM are globally produced each year [1]. CM is a vital fertilizer resource for farming and gardening [2] because it is rich in organic matter and essential plant nutrients such as nitrogen, phosphorous, calcium and potassium [3,4]. However, CM contains many pathogens, parasite ova, and toxic substances [1], and the direct application of CM into the soil would cause a series of environmental and social problems [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…4 , N 2 O and NH 3 during co-composting of CM and MS. Biolog EcoPlate analysis revealed that PT and MSB enhanced the microbial metabolism involved in carbohydrates, esters and carboxylic acids throughout the composting period. The emissions of CH 4 , N 2 O and NH 3 were significantly associated with microbial metabolism, which was influenced by temperature, NH 4…”
mentioning
confidence: 99%